AB0103 Tacrolimus Inhibit IL-1β and ER Stress-Induced, Rankl-Mediated Osteoclastogenesis by Inhibiting Perk, Ire1, Grp78, Eif2a, C-Fos and Nfatc1. (10th June 2014) - Lee, W.-S.; Lee, E.-G.; Sung, M.-S.; Lee, C.-H.; Lee, M.-S.; Yoo, W.-H.
Abstract : Background: Tacrolimus (TAC) is a T cell specific, anti-inflammatory agent that has been used as a therapeutic agent for rheumatoid arthritis (RA). IL-1β and thapsigargin (TG)-induced endoplasmic reticulum (ER) stress modulate the receptor activator of nuclear factor kappa-B ligand (RANKL)-mediated osteoclastogenesis. Objectives: This study was investigated to define the effects of TAC on IL-1β and ER stress-induced, RANKL-mediated osteoclastogenesis and its mechanisms. Methods: Bone marrow cells (BMCs) were obtained from 5-week-old male ICR mice and cultured to be differentiated into osteoclasts with M-CSF and RANKL in the presence or absence of IL-1β, TG, or TAC. The formation of osteoclasts was evaluated by tartrate-resistant acid phosphatase (TRAP) staining and resorption pit assay with dentine slice. The molecular mechanisms of the above effects of TAC on osteoclastogenesis were investigated by using RT-PCR and immunoblotting for osteoclast specific and ER stress signaling molecules, including PERK, IRE1, GRP78, eIF2α, c-Fos and NFATc1. Results: IL-1β and TG-induced ER stress increased the formation of osteoclasts by up-regulating the osteoclast specific signals (c-Fos, NFATc1) and ER stress-associated signaling pathways (PERK, IRE1, GRP78, and eIF2α). TAC significantly inhibited IL-1β and ER stress-induced, RANKL-mediated osteoclastogenesis by down-regulating above signal pathways, dose-dependently. Conclusions: TAC inhibited IL-1β and ER stress-induced, RANKL-mediated osteoclastogenesis by inhibiting intracellular signaling pathways, including PERK, IRE1, GRP78, c-Fos and NFATc1. These results suggest that TAC might have disease modifying effects by inhibition of inflammation and ER stress-induced osteoclastogenesis in the inflammatory joint diseases, such as RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4216